Adult onset cryopyrin-associated periodic syndrome due to germline missense mutation in NLRP3 in a previously healthy middle-aged woman - Cho, Sung Ik; Kim, Sheehyun; Kim, Ju Yeon; Kim, Jeong-Won; Pyeon, Sujin; Lee, Won-Woo; Park, Jin Kyun (Frontiers in Immunology, 2025)
BackgroundCryopyrin-associated periodic syndrome (CAPS) is an autoinflammatory disease caused by a gain-of-function mutation in the NLRP3 gene, which regulates inflammasome-mediated interleukin-1β (IL-1β) production. This leads to recurrent episodes of fever, rash, and arthritis, typically beginning in childhood.ObjectiveTo demonstrate the role of a missense mutation, c.386A>G, in NLRP3 in adult-onset CAPS in a previously healthy middle-aged woman.MethodsWhole-exome sequencing was performed. Serum levels of IL-1β, interleukin-1 receptor antagonist (IL-1RA), and tumor necrosis factor α (TNF-α) were measured. CD14-positive monocytes, isolated from the patient before and during IL-1 inhibition therapy, were stimulated with lipopolysaccharide (LPS), and cytokine production was assessed.ResultsA 47-year-old woman presented with recurrent periorbital swelling and inflammatory symptoms, along with elevated IL-1RA and IL-6 levels. Genetic analysis revealed a heterozygous missense mutation in the NLRP3 gene (NM_001243133, c.386A>G, p.Lys129Arg). Serum IL-1RA levels were significantly elevated during active disease. Monocytes from the patient produced high levels of IL-1β and TNF-α upon LPS stimulation. Treatment with anakinra ameliorated all symptoms and normalized inflammatory cytokine overproduction in the monocytes.ConclusionWe report a case of adult-onset CAPS in a previously healthy woman, caused by a missense mutation (c.386A>G) in the NLRP3 gene, who exhibited a remarkable response to anakinra treatment. Autoinflammatory diseases should be considered in patients presenting with fever, skin rashes, and systemic symptoms, regardless of age.